An Analysis of the Training Motivation of Track and Field Athletes at PASI Kediri City for the 2025/2026 Season - Sinta Adela Puspita Basiru (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study analyzes the training motivation of track and field athletes at the PASI Kediri City in 2025-2026 through a qualitative case study approach. Findings indicate that intrinsic and extrinsic motivation play a major role in athlete development, with barriers such as burnout and lack of external support. The study aimed to analyze the training motivation of track and field athletes at the PASI Kediri City and identify these barriers. The focus was on key informants: the head of PASI, coaches, and experienced competitive track athletes. A descriptive qualitative approach was used, using participant observation, in-depth interviews, and documentation as data collection techniques. Data analysis included data reduction, presentation, and drawing conclusions, validated through triangulation of sources, methods, and observer persistence. The study's findings revealed that intrinsic motivation encompasses a love of sport, self-challenge, and personal satisfaction; extrinsic motivation encompasses rewards, family support, and career opportunities. Internal barriers (burnout, loss of confidence) and external barriers (lack of facilities, social pressure) influence training commitment. The study recommends training based on Self-Determination Theory for motivational balance.